#### Answer

$i$

#### Work Step by Step

$i^{33}=i^{32+1}=i^{32}\times i=(i^{2})^{16}\times i=(-1)^{16}\times i=1\times i=i$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
978-0-13-421743-7

ISBN 13:
978-0-13421-743-7

$i$

$i^{33}=i^{32+1}=i^{32}\times i=(i^{2})^{16}\times i=(-1)^{16}\times i=1\times i=i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.